Strukturisasi Entity Relationship Diagram dan Data Flow Diagram Berbasis Business Event-Driven - Suroto Adi; Desi Maya Kristin (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Entity relationship diagram (ERD) and data flow diagram (DFD) modeling are necessary parts in analysis and design of structured information systems in business. Definition of entities in the ERD, the process, and datastore in the DFD have well described in a lot of literatures. However, practically it is not easy to explain how to design ERD and DFD models so that the students well understand the modeling steps, especially in business applications. This study discussed step-by-step systematic approach to ERD and DFD modeling using "business event-driven" approach that is represented by the REA model, through structuring REA-ERD and REA-DFD. From the results we concluded that the logical design of ERD should be done before designing DFD, so that there would be perfect "balancing" between the entities in the ERD and data stores in the DFD. Consequently, the implementation of these steps needed to be tested both qualitatively and quantitatively in advanced researches